Anjuran Menikah dan Memperbanyak Keturunan Studi Hadis atas Fenomena Childfree di Masyarakat - Fiqi Halwaini; Wiwin Fauziyah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The Childfree phenomenon is still hotly discussed , especially on Indonesian social media. This phenomenon is quite controversial because in the construction of Indonesian society. Children are a gift and also one of the goals of marriage. Indonesia, which has a pronatalist culture, gives important consideration to Childfree’s views in the country. Thus, this is an interesting thing to explore, namely the study of the childfree phenomenon from a hadith perspective using thematic methods. By conducting this research, it is hoped that the meaning and understanding of hadith related to the childfree phenomenon can be used as a referance for understanding that does not only focus on the legal realm. The results of these findings are that the hadiths related to the theme of childfree, namely the hadith about the recomendation for marriage and increasing offspring, do not directly say that childfree is prohibited and opposed in religion.